Odpowiedzi

2010-03-28T16:34:39+02:00
A)4/x=5/9 | * 9x
36 = 5x |:5
x = 5 ⅕
b)x/12=1,2/4 | *12
x = 3,6
c)3,2/2,8=x/3,5 | *9,8
11,2 = 2,8x | :2,8
x = 4
d)9,36/7,2=1,3/x |*7,2x
9,36x = 9,36 | : 9,36
x = 1
e)0,6/x=0,8/6 | * 6x
3,6 = 0,8x | : 0,8
x = 4,5
f)x/0,6=6/0,8 | * 0,48
0,8x = 3,6 | : 0,8
x = 4,5
g)x-5/7=3/5 | * 35
35x - 25 = 21 | +25
35x = 46 | : 35
x = 1,31
h)x/3=x+5/2 | * 6
2x = 6x +15 |-6x
-4x = 15 | : (-4)
x = -3,75
i)4/x+6=5/7+x | * 7x
28 + 42x = 5x + x² | - 5x - x² - 28
37x - x² = -28
x (37 - x) = - 28 | : (37 - x)
x = -28/(37-x)

Najlepsza Odpowiedź!
2010-03-28T16:40:30+02:00
A)4/x=5/9
5x = 4*9
5x = 36
x = 36/5
x = 7,2

b)x/12=1,2/4
4x = 1,2*12
4x = 144/10 /:4
x = 36/10
x = 3,6

c)3,2/2,8=x/3,5
2,8x = 3,2*3,5
2,8x = 56/5 /:2,8
x = 28/7
x = 4

d)9,36/7,2=1,3/x
9,36x = 1,3*7,2
9,36x = 234/25 /:9,36
x = 936/936
x = 1

e)0,6/x=0,8/6
0,8x = 6*0,6
0,8x = 3,6 /:0,8
x = 9/2
x = 4,5

f)x/0,6=6/0,8
0,8x = 6*0,6
0,8x = 3,6 /:0,8
x = 9/2
x = 4,5

g)x-5/7=3/5
5(x-5) = 3*7
5x-25 = 21
5x = 21+25
5x = 46 /:5
x = 9,2

h)x/3=x+5/2
3(x+5) = 2x
3x+15 = 2x
3x-2x = -15
x = -15

i)4/x+6=5/7+x
5(x+6) = 4(7+x)
5x+30 = 28+4x
5x-4x = 28-30
x = -2